Pedagogical practices of physics teachers from the Catatumbo region, Colombia (2020)
Pedagogical practice allows teachers to focus their attention on three types of knowledge: disciplinary knowledge: what do I know, pedagogical knowledge: how do I communicate what I know, and academic knowledge: how do I transform myself with what I know? Thus, the teacher has the capacity to transform not only his or her students, but to transform himself or herself in the process. In this sense, the research aims to characterize the pedagogical practice of physics teachers in educational institutions located in the “Catatumbo, Colombia”, a region characterized by high levels of violence and very specific social situations; it also aims to determine the influence of training at the master's level of the Francisco de Paula Santander University on teachers working in the area of physics. The research, framed in the mixed paradigm, allows the realization of univariate and multivariate analysis of variables inherent to the process of training and professional action of master teachers, as well as the categorization of their experiences resulting from the application of knowledge obtained throughout their studies in their professional practice and training in different areas of knowledge, emphasizing the practices, laboratories and teaching strategies used in the training of students by physics teachers.